PHILOSOPHY OF THE EPOCH AND THE PERSONALITY’S TYPE OF OUR TIME - Vladimir, Shedyakov (Collection of scientific papers «ΛΌГOΣ», 2025)
Flexible consideration of the diversity of interests of groups and classes of the population (primarily in the creation of environment for security and development), providing everyone with opportunities to develop their abilities and their pro-social creative realization is a condition for the sustainable promotion of the cultural-civilizational world to an ascending orbit, increasing the level of justice in society, and eliminating property stratification.